Penggunaan Key Opinion Leader sebagai Alat Pemasaran Media Sosial di PT Mitra Aktif Adiperkasa Tbk - Onggo, Fillanta Ferent; Ananda, Denta Felli; Danibrata, Aulia; Briliana, Vita (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2023)
This internship report is intended to explain the author's activities during the internship at PT. MAP Active Adiperkasa Tbk through the Magang Bersertifikat Kampus Merdeka program. This program is aimed at increasing self-competence through work experience, so that it fits the needs of the world of work and the industry you want to target. This report will explain how the author is daily life as part of the retail marketing division. The things that will be explained include the division of tasks within the marketing team, all work assigned by the supervisor to the author, and the final assignment which involves collaboration between the supervisor and the writer which is called the Innovation Project.